Multidetector CT Angiography of the Aortoiliac System and Lower Extremities: A Prospective Comparison with Digital Subtraction Angiography - Martin, Michael L; Tay, Kiang H; Flak, Borys; Fry, Peter D; Doyle, D. Lynn; Taylor, David C; Hsiang, York N; Machan, Lindsay S (American journal of roentgenology (1976), 2003)
Our objective was to determine whether multidetector CT (MDCT) angiography is an accurate and reliable method of revealing atheroocclusive disease of the aortoiliac system and the lower extremities compared with digital subtraction angiography (DSA). Forty-one patients with ischemic legs underwent both MDCT angiography and DSA of the aortoiliac system and the legs. The arterial supply of the legs was divided into 35 segments. Three independent observers rated each segment according to the maximal degree of arterial stenosis. Consensus interpretation was used to calculate the sensitivity and specificity of MDCT angiography in showing arterial occlusions and stenoses of at least 75%. Intertechnique agreement was measured for each anatomic segment, and interobserver agreement was calculated for both techniques. Agreement was quantified using the kappa statistic. The sensitivity and specificity of MDCT angiography for depicting arterial occlusions and stenoses of at least 75% were 88.6% and 97.7%, and 92.2% and 96.8%, respectively. Substantial intertechnique agreement (kappa > 0.4) was present in 102 (97.1%) of 105 arterial segments. Substantial interobserver agreement was present in 104 (99.0%) of 105 comparisons for both MDCT angiography and DSA with an average kappa value of 0.84 for CT and 0.78 for DSA. MDCT angiography showed more patent segments than DSA (1192 vs 1091). All nine segments seen on DSA and not seen on MDCT angiography were in the calves. Of 110 segments seen on MDCT angiography and not seen on DSA, 100 (90.9%) were in the calves. MDCT angiography was accurate in showing arterial atheroocclusive disease with reliability similar to DSA. MDCT angiography showed more vascular segments than DSA, particularly within calf vessels.